Cassava bagasse as a dietary food product - Leonel, M. [UNESP]; Cereda, M. P. [UNESP]; Roau, X. [UNESP] (My University, 1998)
Cassava bagasse, the solid residue of the starch industry, was studied as a potential ingredient in high-fibre dietary products. The bagasse contained 80% of starch, 11.5% fibre, 1.14% ash and 0.85% of protein, and it had a pH of 5.8. Glucose was the major sugar and the hemicellulose content was 22.31%. Microscopic analysis of the bagasse revealed a large number of starch granules inside the parenchyma cells and fibres, as well as outside the cells. The bagasse may be used in high-fibre products, and total or partial hydrolysis of its starch content might increase its commercial value.
Keywords: Cassava; Dietary foods; Fibres; Residue